The northern cross fast radio burst project – II. Monitoring of repeating FRB 20180916B, 20181030A, 20200120E, and 20201124A. Issue 2 (13th April 2022) - Trudu, M; Pilia, M; Bernardi, G; Addis, A; Bianchi, G; Magro, A; Naldi, G; Pelliciari, D; Pupillo, G; Setti, G; Bortolotti, C; Casentini, C; et al.
ABSTRACT: In this work, we report the results of a 19-month fast radio burst observational campaign carried out with the north–south arm of the Medicina Northern Cross radio telescope at 408 MHz in which we monitored four repeating sources: FRB20180916B, FRB20181030A, FRB20200120E, and FRB20201124A. We present the current state of the instrument and the detection and characterization of three bursts from FRB20180916B. Given our observing time, our detections are consistent with the event number we expect from the known burst rate (2.7 ± 1.9 above our 10σ, 38 Jy ms detection threshold) in the 5.2 d active window of the source, further confirming the source periodicity. We detect no bursts from the other sources. We turn this result into a 95 per cent confidence level lower limit on the slope of the differential fluence distribution α to be α > 2.1 and α > 2.2 for FRB20181030A and FRB20200120E, respectively. Given the known rate for FRB20201124A, we expect 1.0 ± 1.1 bursts from our campaign, consistent with our non-detection.